Riprap protection of propeller-induced scour at quay structure - Yeo, Zi Xin (Nanyang Technological University, 2022)
Multiple technological developments in maritime trade has resulted in larger ships with a stronger and more complicated propulsion system. The high velocity of the propeller jet has increased scouring action to the berth bed along quay structures, leading to the degradation of key port infrastructure and subsequent port instability and failure. In response, PIANC, the World Association for Waterborne Transport Infrastructure, published their report Guidelines for Protecting Berthing Structures from Scour Caused by Ships, PIANC Report No. 180 to help engineers design proper scour protection. Two key methods for rock stability are listed in the report- German and Dutch. However, both are incomplete. This study aims to expand upon experiments done by Tan [1] and Ang [2] to determine the effectiveness of riprap protection against scour. A propeller jet was made to directly impinge upon a vertical wall to determine the critical efflux velocity when shear failure of the riprap occurs. Five different rock diameters, vertical wall clearance and horizontal wall clearances were used in this study. The results found confirmed previous relationships found by Tan [1] and Ang [2], where critical efflux velocity increases proportionately to horizontal and vertical wall clearances. Further, mean values of both German and Dutch methods combined were compared against results from this study and were found to be conservative at greater rock diameter. From the results, an empirical relationship between critical efflux velocity, propeller diameter, vertical and horizontal clearance, as well as rock diameter was represented in an equation. This proposed equation can aid with future design of riprap by identifying critical efflux velocity conditions.